Analisa Topik Pendidikan Dalam Al-Quran dengan Pendekatan Text Mining - Bustami Yusuf; Muhammad Zaeki; Hendri Ahmadian; Khairan Ar; Sri Wahyuni (Fakultas Teknik, 2021)
Education is one of the sciences that makes humans much better by learning various scientific disciplines. Al-Quran is one of the sources of knowledge that is believed by Muslims around the world. Because technology has penetrated almost every domain of our lives , including the world of education. Thus, the authors make technology as tool for researching educational topics in Al-Quran by implementing text exploration .The research was carried out by making some basic words that were related to the subject of education as the keywords in this study. The keywords are “Ajar”, “Bicara”, “Cipta”, “Dengar”, “Ingat” and “Lihat”. Then, the authors implemented the Naïve Bayes Classifier algorithm. To test and evaluate the results, the author used two methods, i.e. recall and precision. The study results are the keyword “cipta” by 3.05 %, “Ingat” 2.25 %, “Ajar” 1.96 %,“Lihat” 0.82 %, finally “Dengar” 0.62% and “Bicara” 0.34% with total weight of 3,516 words that have been filtered. The overall percentage of the results is 9.04% of the total number of words 38,761 in the Al-Quran. For the Naïve Bayes algorithm evaluation method, the recall and precision scores are 0.605 and 0.366, respectively.